Im dalej w las… - Gralewicz-Wolny, Iwona (Paidia i Literatura, 2019)
The article focuses on Ten i tamten las [This and That Forest] by Magdalena Tulli, which is another recent example of a book addressed to children, whose sender is a distinguished author of adult literature. The interpretation of the text reveals the adult problems and emotions faced by its animal heroes, subtly hidden behind the adventurous layer of the work. Consequently, the reader receives a book that defies the traditional division into children’s literature and adult literature: a book that requires not so much the right metrics as sensitivity.